2d Mxene/ 1d Gan Van Der Waals Heterojunction for Self-Powered Uv Photodetector - Radhalayam, D (American Institute of Physics, 2023)
MXene s two-dimensional (2D) morphology, metallic electrical conductivity, and optical transparency characteristics have been widely utilized to uplift the performance of diverse optoelectronic devices. In this study, we demonstrate a simple spin-coating of 2D MXene nanosheets on 1D GaN nanorods (NRs) to establish a van der Waals (vdW) Schottky junction, which is efficient to detect UV radiation (λ = 382 nm) without requiring the external power supply. The built-in electric field developed through vdW Schottky junction formation stimulates the separation of electron-hole pairs and thereby facilitates the MXene/GaN NRs device to exhibit better UV detection performance than the pristine GaN NRs device. The performance of both pristine GaN and MXene/GaN NRs devices is compared by tuning the UV radiation power density in the range of 0.33-1.35 mW/cm2. Notably, the self-powered MXene/GaN NRs photodetector demonstrated the characteristics of high photoresponsivity (48.6 mA/W), detectivity (5.9 <FOR VERIFICATION> × 1012 Jones), and external quantum efficiency (543%). These characteristics signify the suitability of MXene/GaN self-powered photodetectors for various applications, including imaging, sensing networks, and energy-saving communication. © 2023 Author(s).